Acetabular Liner Dissociation following Total Hip Arthroplasty: A Rare but Serious Complication That May Be Easily Misinterpreted in the Emergency Department. (12th October 2015) - O'Neill, Christopher K. J.; Napier, Richard J.; Diamond, Owen J.; O'Brien, Seamus; Beverland, David E.
Abstract : Acetabular liner dissociation is a rare complication of Total Hip Arthroplasty (THA) which requires urgent revision surgery. A case is presented in which the correct diagnosis was not appreciated on two separate Emergency Department attendances. The typical symptoms, signs, and radiological features are outlined and the importance of considering a rare complication following a commonly performed procedure is highlighted.